Lover unveiled - Ward, J. R., 1969- (Ward, J. R., 1969- Black dagger brotherhood series., 2021)
"Sahvage has been living under the radar for centuries-and he has every intention of staying "dead and buried." But when a civilian female sucks him into her dangerous battle with an evil as ancient as time, his protective side overrides his common sense. Mae has lost everything, and desperation sets her on a collision course with fate. Determined to reverse a tragedy, she goes where mortals should fear to tread-and comes face-to-face with the Brotherhood's new enemy. She also discovers a love she never expected to find with Sahvage, but there can be no future for them. Knowing they will part, the two band together to fight against what Mae unknowingly unleashed-as the Brotherhood closes in to reclaim one of their damned, and the evil vows to destroy them all. . . "--